Summary of SFRP-IRPA workshops on the reasonableness in the practical implementation of the ALARA principle - Lecomte, Jean-François; Bannon, Amber; Billarand, Yann; Bryant, Peter; Cantone, Marie-Claire; Coates, Roger; Croft, John; Jean-François, Stéphane; Le Guen, Bernard; Schieber, Caroline; Schneider, Thierry (Radioprotection, 2019)
The practical implementation of the principle of optimisation of radiological protection (i.e., ALARA principle) was the subject of two workshops organised in Paris (France) in February 2017 and October 2018 at the initiative of SFRP within the framework of IRPA. The article summarizes the discussions and conclusions of these two workshops. The search for reasonableness was examined in three sectors: nuclear industry, medical practices and existing exposure situations. In all sectors, the optimisation remains a challenge and experience shows that this is implemented through a deliberative process to achieve a reasonable compromise with all informed parties. This issue was further investigated by three working groups − one for each sector – on the basis of cases studies. It emerges that, in complement to the use of classical tools such as cost-benefit analysis, the implementation of the optimisation principle implies a clear identification of the challenges to be met in order to achieve the best protection in the prevailing circumstances. These challenges may be specific to a type of exposure situation and in some cases to a given situation. The process should also well identify the relevant stakeholders and decision-makers to be involved and determine how they will be involved. A proactive process including development of awareness, empowerment and/or training may be needed. This reflexion deserves to be further developed.